Radiation characteristics of inclined slot antenna on conducting spherical cavity - Phongcharoenpanich, C.; Boonrod, D.; Krairiksh, M. (My University, 2003)
This paper presents theoretical investigations of the characteristics such as radiation pattern, half-power beamwidth, directivity, front-to-back ratio and polarization of an inclined slot on spherical surface. The total fields inside the cavity are formulated by means of the combination of TE and TM modes. The unknown coefficients of the fields are determined by imposing the boundary conditions. The voltage distribution along the slot is reasonably assumed to be the sinusoidal functions. The numerical results of radiation characteristics for various radii of the spherical surface are illustrated. The comparisons between horizontal slot and inclined slot are reported. The result of the analysis shows that this technique is very useful for the design of spherical slot array antenna of any orientation.
Keywords: Antenna radiation patterns; Boundary conditions; Electromagnetic fields; Equations; Information technology; Polarization; Slot antennas; Tellurium; Voltage; Wireless communication